KEPEMIMPINAN PEMERINTAHAN DALAM MEMPERBAIKI JALAN DI KABUPATEN SIMALUNGUN PADA TAHUN 2021 - Dwi Fadillah Nimas Utari; Hasanuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Government leadership in this study is the ability of the Simalungun Regency Government to repair roads. The Simalungun Regency Government in 2021 has a program that distinguishes its leadership from the leadership of the previous Regent, namely the "Marharoan Bolon" program which is an alternative to road infrastructure development by maximizing human resources. This study aims to describe the Leadership of the Regent and the Head of the Public Works Office in Repairing Roads, as well as identifying factors that influence their Government Leadership. This research method uses a qualitative method with a descriptive approach. The type of data used in this writing is primary data derived from research results that the author obtained through interviews with relevant informants and documentation at the research location, as well as secondary data in the form of related documents that the author obtained during this research. The research found that the government leadership in Simalungun Regency in repairing roads in 2021 has begun to show differences compared to the leadership of the previous Government. Leaders in Simalungun Regency have tried to maximize resources and strive for the best in managing road infrastructure development in 2021 through the "Marharoan Bolon" program, but have not succeeded in solving the problem of road repair due to limited human resources from both the government and the community, budget issues, and also the conditions of the Covid-19 pandemic which resulted in the delay of several planned programs. Keywords: Government Leadership, Leadership Functions, Repairing Roads